PENGGUNAAN HEDGES DALAM KONFERENSI PERS DONALD TRUMP TERKAIT PANDEMI COVID-19: KAJIAN LINGUISTIK PRAGMATIK - Tajirah Umajjah (Universitas Hasanuddin, 2022)
This research is pragmatic research that aims to (1) classify the types of hedges used by Donald Trump in press conferences related to Covid-19; (2) find initial assumptions or presuppositions against hedges used by Donald Trump at press conferences related to Covid-19; (3) find the true meaning of implicatures in the hedges used by Donald Trump at press conferences related to Covid-19. The figure whose words are the object of this research is the 45th President of the United States, Donald Trump at a press conference to the Covid-19. Trump is a representative of world leaders where the leaders of a country should no longer convey hedges to their people who need certainty. The research results in this thesis include the types of hedges Adverbials (40 data), Epistemic (5 data), Modal Verb (20 data), Cognition Verb (89 data) Hypothetical (126 data), and Anticipatory (14 data).